An Analysis of the Environmental Impact Management of Tingal Irrigation Scheme in Temanggung Regency - Widodo Brontowiyono (International Journal of Science and Society, 2020)
A study of the environmental impacts of Tingal Irrigation Scheme should be conducted to derive maximum benefits from the project development and management. This research aimed to identify the pre-existing environmental conditions, describe the expected potential impacts, and recommend some methods to manage and monitor the impacts. The analysis results indicated that the pre-existing environmental conditions of the study area were generally good, different types of impacts potentially arose from each stage of the development, and each type of impacts required specific, detailed management and monitoring.